2011
DOI: 10.1007/s11904-011-0098-0
|View full text |Cite
|
Sign up to set email alerts
|

Women and Vulnerability to HAART Non-Adherence: A Literature Review of Treatment Adherence by Gender from 2000 to 2011

Abstract: A literature review of original research articles on adherence to antiretroviral therapy (ART) in developed countries, covering January 2000 to June 2011, was conducted to determine if gender differences exist in the prevalence of nonadherence to ART. Of the 1,255 articles reviewed, only 189 included data on the proportion of the study population that was adherent and only 57 (30.2%) of these reported proportional adherence values by gender. While comparing articles was challenging because of varied reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 91 publications
(75 reference statements)
5
95
3
2
Order By: Relevance
“…29 Prior studies have reported that older individuals, 30 women, 31 and individuals with low income, 30 depression, 30 polypharmacy, 30 and less morbidity 30 are less likely to be adherent; the association we observed between black race and statin nonadherence did not change appreciably after adjustment for these variables. Reasons for racial differences in adherence likely extend beyond demographics, socioeconomic status, and comorbidities.…”
contrasting
confidence: 45%
See 1 more Smart Citation
“…29 Prior studies have reported that older individuals, 30 women, 31 and individuals with low income, 30 depression, 30 polypharmacy, 30 and less morbidity 30 are less likely to be adherent; the association we observed between black race and statin nonadherence did not change appreciably after adjustment for these variables. Reasons for racial differences in adherence likely extend beyond demographics, socioeconomic status, and comorbidities.…”
contrasting
confidence: 45%
“…Using the 5% sample from the Centers for Medicare and Medicaid Services (CMS), we conducted a retrospective cohort study of white and black Medicare beneficiaries hospitalized for an ischemic stroke between January 1, 2007, and December 31,2012. Data were obtained from Medicare enrollment, inpatient (Medicare part A), outpatient (Medicare part B), and prescription drug (Medicare part D) files.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a growing body of literature showing that females have a lower rate of adherence than males, possibly because females put others before their own health. 10,[21][22][23] In the commercial population, older beneficiaries had consistently higher adherence than their younger counterparts. Younger beneficiaries possibly see adherence to their medication as less of a priority than older individuals.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…data analytic plan First, descriptive statistics were produced for all study variables. Second, age, gender, ethnicity, and education level were considered as covariates, using Pearson correlations and chi-square tests, as these demographic variables have been shown previously to be significantly associated with objective adherence to ART, viral load, and/or CD4 cell count (Golin et al, 2002;Hinkin et al, 2004;Puskas et al, 2011;Smith et al, 2004). We also conducted a manipulation check to evaluate whether participants' ratings of distress actually increased during the behavioral distress tolerance task (i.e., MTPT-C).…”
Section: Mirror-tracing Persistence Taskmentioning
confidence: 99%